2020
DOI: 10.3153/fh20010
|View full text |Cite
|
Sign up to set email alerts
|

Health effects of ethanolic extract from seeds of lady finger

Abstract: Health benefits of lady finger were explored in this study by which the ethanol extract from the seeds was utilized for testing. In high glucose (350 mmole/L) medium, the proliferative activity of C2C12 cells was inferior, but their viability was improved following treated with the extract. The activities of antioxidant enzymes, superoxide dismutase (SOD) and catalase (CAT), were also enhanced. In response to such high glucose concentration, glucose uptake ability of these cells was compromised. The extract wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Gou et al 22 also showed that 150 μg mL −1 okra inhibited the IL-6 mRNA expression in high fat induced-human aortic endothelial cells. Kaewsrichan et al 20 indicated that 1.25 and 2.5 mg mL −1 okra seed ethanolic extract inhibited the TNF-α and IL-6 release in the inflamed cell lines of an L929 mouse fibroblast, PC12 rat adrenal gland, and C2C12 mouse myoblast. Yan et al 21 indicated that 12.5, 25, 50, and 100 μg mL −1 okra polysaccharide decreased the release and mRNA expression of IL-6 and TNF-α in LPS-stimulated BV-2 microglia cells, whereas it did not affect the IL-1β…”
Section: In Vitro Studiesmentioning
confidence: 99%
“…Gou et al 22 also showed that 150 μg mL −1 okra inhibited the IL-6 mRNA expression in high fat induced-human aortic endothelial cells. Kaewsrichan et al 20 indicated that 1.25 and 2.5 mg mL −1 okra seed ethanolic extract inhibited the TNF-α and IL-6 release in the inflamed cell lines of an L929 mouse fibroblast, PC12 rat adrenal gland, and C2C12 mouse myoblast. Yan et al 21 indicated that 12.5, 25, 50, and 100 μg mL −1 okra polysaccharide decreased the release and mRNA expression of IL-6 and TNF-α in LPS-stimulated BV-2 microglia cells, whereas it did not affect the IL-1β…”
Section: In Vitro Studiesmentioning
confidence: 99%